The relation between responsibility and anxiety level in students’ group - Nasirova, Nigar (Asian Journal of Contemporary Education, 2025)
Education process in a higher educational institution is a complex, multifaceted process that places high demands on the health, plasticity and flexibility of mental and physiological processes of young people. In this study, it is aimed to examine the relationship between responsibility and anxiety level of students who continue their education in the social sciences faculty of a Baku State University. The small group of university students consists of fifty people between the ages of 18 and 21 participated in the study. The study attempted to understand anxiety level of the students, and responsibility. Demographic information of the participants, daily activities, habits, academic results were recorded as independent variables, anxiety level was differentiated as dependent factor. The study was examined based on constructive approach using assessment scale. Participants' anxiety level was evaluated with the GAD-7 (Generalized anxiety disorder-7) assessment scale. University students experience different academic stresses. Academic pressures caused by lack of time management, and irresponsible behavior can be a significant source of stress. This situation negatively affects students' mental and physical health. Poor time management, irresponsible behaviors of university students can lead to low academic success and psychological problems. They experience these stress and anxiety symptoms especially during the midterm final exams. As time management skills develop, an increase in academic average is observed. It was found that there was a relationship between the students' responsibility, academic achievement and anxiety level. The results of the research can be effective for university administration, department and faculty members. Moreover the development of the future research would be continued by other researchers’ team to explore coping skills, stress management abilities of students with large samples.